2018
DOI: 10.1038/s41386-018-0305-4
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the histone di-methyltransferase G9a in nucleus accumbens shell decreases cocaine self-administration, stress-induced reinstatement, and anxiety

Abstract: Comorbid neuropsychiatric disorders such as addiction and anxiety could involve common underlying mechanisms. One potential mechanism involves epigenetic regulation of histone 3 dimethylation at lysine 9 residues (H3K9me2) by the histone dimethyltransferase G9a. Here we provide evidence that local AAV-RNAi-mediated knockdown of G9a expression in nucleus accumbens shell (NAcSh) of male rats reduces both addictive-related and anxiety-related behaviors. Specifically, G9a knockdown reduces sensitivity to low dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 43 publications
(65 reference statements)
3
24
0
Order By: Relevance
“…For example, changes in DNA methylation could be responsible for neuroplasticity changes induced by addictive drugs, such as repeated cocaine administration reduced global levels of H3K9 dimethylation in the NAc, which correlates with changes in dendritic spines (Maze et al, 2010). Also, changes of the histone dimethyltransferase G9a in the NAc shell actively affect cocaine self-administration in rats (Anderson et al, 2018(Anderson et al, , 2019. Of importance, DNA methylation in NAc during drug addiction seems to respond to a time-dependent regulation, enhancing DNA methylation in the NAc after 30 days of cocaine withdrawal (Massart et al, 2015), suggesting that an increase in DNA methylation is responsible for cocaine craving.…”
Section: Discussionmentioning
confidence: 99%
“…For example, changes in DNA methylation could be responsible for neuroplasticity changes induced by addictive drugs, such as repeated cocaine administration reduced global levels of H3K9 dimethylation in the NAc, which correlates with changes in dendritic spines (Maze et al, 2010). Also, changes of the histone dimethyltransferase G9a in the NAc shell actively affect cocaine self-administration in rats (Anderson et al, 2018(Anderson et al, , 2019. Of importance, DNA methylation in NAc during drug addiction seems to respond to a time-dependent regulation, enhancing DNA methylation in the NAc after 30 days of cocaine withdrawal (Massart et al, 2015), suggesting that an increase in DNA methylation is responsible for cocaine craving.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, we found that cocaine treatment increased KMT1C/G9A and decreased KDM1A/LSD1 enzymes. KMT1C/G9A is a key mediator of the epigenetic effects of cocaine in the mesolimbic system (Maze et al, 2010;Anderson et al, 2019) and has been described as a crucial epigenetic marker of heterochromatin formation during meiosis (Tachibana et al, 2007). KDM1A/LSD1 participates in the demethylation of H3K4/K9 and is required for spermatogonial differentiation and germ cell survival in mice (Myrick et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The NAcSh has been mostly studied for its role in reward and appetitive behaviors ( Nicola, 2007 ; Floresco, 2015 ; Namburi et al, 2016 ). However, there is ample evidence that the NAcSh regulates defensive responses ( Reynolds and Berridge, 2001 , 2002 , 2003 , 2008 ; Newton et al, 2002 ; Barrot et al, 2005 ; Al-Hasani et al, 2015 ; Ramirez et al, 2015 ; Zhu et al, 2016 ; Anderson et al, 2018 ; Lee et al, 2018 ; Piantadosi et al, 2018 ) including anxiety ( Martinez et al, 2002 ; Lopes et al, 2007 , 2012 ; da Cunha et al, 2008 ). It is generally accepted that the striatum including the NAcSh integrates cognitive and affective information from the cortex and thalamus in a way that leads to the selection or promotion of an appropriate behavioral response ( Nicola, 2007 ; Floresco, 2015 ; Namburi et al, 2016 ) especially where the outcome of an action is ambiguous ( Namburi et al, 2016 ).…”
Section: The Brain Anxiety Networkmentioning
confidence: 99%